View Christian Philosophy Concerning the existence of God - Samuel Bartolo; Mozes Lawalata (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
This article explores Christian philosophical views regarding the existence of God through an analysis of various main arguments that have been developed by Christian philosophers. Focusing on ontological, cosmological, teleological, and moral arguments, this article explores how each argument attempts to prove the existence of God through rational and empirical approaches. Ontological arguments, such as those proposed by Anselm of Canterbury, use conceptual reflection to conclude that God must exist. The cosmological argument, popularized by Thomas Aquinas, combines observations of the universe with the logic of causality to demonstrate the existence of a transcendent first cause. The teleological argument, with a major contribution from William Paley, suggests that the complexity and order in the universe indicates the existence of an intelligent designer. Apart from that, this article also highlights the importance of religious experience as subjective evidence of the existence of God. Through a combination of rational argument and spiritual experience, Christian philosophy offers a comprehensive and insightful view of God's existence, making it relevant in contemporary theological and philosophical discussions.